Optimization of laser welding of tri – metal joint via response surface methodology - Kumar, G. Krishna; Velmurugan, C.; Kannan, T. (JOURNAL OF ADVANCES IN CHEMISTRY, 2017)
Â Laser welding input parameters play a major role in determining the quality of a weld joint. In the nuclear power plants, hybrid structures of nickel and steel alloys offer an advantage in comparison to conventional materials, e.g. in heat exchanger tube areas. Due to demand in the nuclear industry for new material combinations based on commercially available and qualified materials, research into thermal joining of dissimilar materials has been initiated. The use of laser for joining mild steel / nickel with 316L austenitic stainless steel filler material and structures offers some advantages compared with usual thermal joining processes. The main aim is the control of phase formation, which occurs during thermal joining of mild steel to nickel. In this research work microstructure study and optimization of laser welding of mild steel / nickel sheets with wire feeding was done using Central Composite Design(CCD) and Response Surface Methodology (RSM) are used to build the mathematical model. By means of the laser power, welding speed and pulse width on the tensile strength model was developed and tested by analysis of variance method (ANOVA), the relationship between process parameters and output response and interaction among the process parameters are analyzed and discussed in detail. The scanning electron microscopes (SEM) with energy dispersive X-ray spectroscopy (EDS) technique were used for microstructure study of the bi-metal and tri-metal joints of the weld.